2015
DOI: 10.1007/s13313-015-0351-x
|View full text |Cite
|
Sign up to set email alerts
|

Culm discolouration as an indicator of Fusarium pseudograminearum biomass

Abstract: Disease severity of crown rot (Fusarium pseudograminearum) in winter cereal culms is typically assessed at harvest maturity by recording incidence of infection, whitehead production and discolouration of basal internodes. This study has investigated the relationship between the proportion of discolouration of individual internodes and the extent of host tissue colonisation by the pathogen, based on species-specific quantitative PCR (qPCR). Field-grown p l ots w er e u se d t o c om pa re vis ua l ra tin gs an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…The current study included a time-course examination of the impact of plant maturation on crown rot disease responses. While assessment was only performed in one year, the findings support those of Knight and Sutherland (2015), in which a plateau or reduction in F. pseudograminearum biomass was observed in two hexaploid spring wheat genotypes at maturity. The current study demonstrated that within cv.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The current study included a time-course examination of the impact of plant maturation on crown rot disease responses. While assessment was only performed in one year, the findings support those of Knight and Sutherland (2015), in which a plateau or reduction in F. pseudograminearum biomass was observed in two hexaploid spring wheat genotypes at maturity. The current study demonstrated that within cv.…”
Section: Discussionsupporting
confidence: 78%
“…Knight et al (2012) described similar variation in cereal seedling tissues, and supported the use of plant tissue dry weights as an alternative normalising factor. bioRxiv Timing of tissue collection may have a strong influence on crown rot disease measurement, along with individual cultivar growth patterns, growth stage and environmental variation (Hogg et al, 2007;Knight et al, 2012;Knight & Sutherland, 2015;Knight & Sutherland, 2016;Knight et al, 2017;Percy et al, 2012;Smiley, 2019;Stephens et al, 2008;Summerell et al, 1989). The current study included a time-course examination of the impact of plant maturation on crown rot disease responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease severity score was calculated by summing the number of tillers in each severity category and multiplying by the value of the category, then dividing by the total number of tillers scored. Significant correlations between disease severity score and both Fusarium populations and yield have been reported (Hogg et al 2007;Knight and Sutherland 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of stem base browning is often used as a proxy for the evaluation of cereal germplasm for FCR resistance. Knight and Sutherland () found positive correlations between stem base browning and fungal biomass measured using qPCR in wheat and barley in a 2‐year field study. However, these correlations were significant for different internodes of infected plants in different years.…”
Section: Breeding For Fcr Resistance and Tolerancementioning
confidence: 99%